Navigating reading challenges: Analyzing the factors behind students' struggles with comprehension - Hermida, Rita (Accentia: Journal of English Language and Education, 2025)
This study investigates the multifaceted challenges students face in reading comprehension, with a focus on identifying key areas of difficulty through a quantitative method in which questionaries distributed to 32 students of English Education Department students in UIN Ar-Raniry Banda Aceh, Indonesia. The results showed that the respondents struggled with general comprehension, underlining the prevalence of cognitive and educational hurdles. The acquisition of vocabulary also appeared as a significant obstacle, with many experiencing troubles understanding word meanings, limiting greater connection with texts. Additionally, most failed to identify key information, which is a fundamental skill for extracting meaning and building knowledge from textual content. Difficulties with reading speed and efficiency also contributed to decreased understanding and retention. Furthermore, they also struggled to synthesize information, demonstrating limits in integrating ideas across texts. These findings highlight the complexities of reading comprehension and the importance of thorough, focused educational strategies. To help students succeed in academic reading tasks, interventions should focus on building vocabulary, reading fluency, and higher-order comprehension skills.